2022
DOI: 10.3389/fnut.2022.852984
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Nutrition Care Through Real-Time, Sensor-Based Capture of Eating Occasions: A Scoping Review

Abstract: As food intake patterns become less structured, different methods of dietary assessment may be required to capture frequently omitted snacks, smaller meals, and the time of day when they are consumed. Incorporating sensors that passively and objectively detect eating behavior may assist in capturing these eating occasions into dietary assessment methods. The aim of this study was to identify and collate sensor-based technologies that are feasible for dietitians to use to assist with performing dietary assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 92 publications
(189 reference statements)
0
12
0
Order By: Relevance
“…These methods may even be superior to CGM-based approaches regarding detection times. Wang and colleagues identified several devices that can quickly detect IA ( 16 ), such as a headband device that can detect eating events via chewing sounds within only 3 min ( 16 , 90 ). Similarly, a pilot study by Kumar and colleagues investigating the use of abdominal sounds to detect IA found an average detection time of only 4.3 min ( 91 ).…”
Section: Discussionmentioning
confidence: 99%
“…These methods may even be superior to CGM-based approaches regarding detection times. Wang and colleagues identified several devices that can quickly detect IA ( 16 ), such as a headband device that can detect eating events via chewing sounds within only 3 min ( 16 , 90 ). Similarly, a pilot study by Kumar and colleagues investigating the use of abdominal sounds to detect IA found an average detection time of only 4.3 min ( 91 ).…”
Section: Discussionmentioning
confidence: 99%
“…Remote technologies to validly assess diet continue to evolve [ 43 , 44 ]. Behavioral measures of how people eat, such as frequency of eating and length of an eating episode, may be gleaned using wrist accelerometry [ 45 ], and the number of bites and eating speed may be measured using an app and smartwatch [ 46 ]. Direct measures of the biochemical and physiological outcomes of medical nutrition therapy, such as blood glucose concentrations (as demonstrated in the Ma et al study [ 30 ]), blood pressure, and body weight [ 14 ], can be conducted remotely, passively, and continuously.…”
Section: Discussionmentioning
confidence: 99%
“…This can be achieved with the use of time-triggered ecological momentary assessment (EMA) to capture food intake and contextual data at pre-determined times personalized to subjects’ usual pattern of food intake [ 73 , 74 ]. Although not yet commercially available nor feasible for use in practice settings [ 75 ], wearable sensors may also be useful for capturing real-time eating behavior [ 76 ]. Sensors embedded in smartwatches can be used to detect eating-related behaviors such as hand-to-mouth movements to deliver timely prompts via a connected device such as a smartphone to remind users to record their dietary intake, minimizing inaccurate dietary recalls because of memory decay [ 77 , 78 ].…”
Section: Discussionmentioning
confidence: 99%